Guardians of the galaxy : Take the Milano and run - Caramagna, Joe (Guardians of the Galaxy, 2018)
"After crash landing on a space station called Conjunction, the Guardians search for Pandorian Crystals while avoiding fighting the Conjunction Arena and being busted by Nova Corpsman Titus"--Publisher.